(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
درسنا في هذا البحث تأثير ورود حزمة إلكترونية على بلازما كثيفة ساخنة غير متجانسة، واللااستقرارات الناتجة في هذه الجملة من خلال دراسة تأثير تغير كثافة البلازما على نمو اللااستقرار في هذه الجملة، حيث تمت دراستها بفرض أن كثافة البلازما من مرتبة غاز فيرمي، وبفرض أن هذه البلازما ساخنة وغير متجانسة، تسقط عليها حزمة إلكترونية باردة وذلك عندما تكون السرعة الطورية صغيرة مقارنة بسرعة هذه الحزمة، وذلك في حالة عدم وجود حقل مغناطيسي خارجي. لقد تم استخراج المعادلات التي تصف هذه الجملة في الحالة التي تكون البلازما تصادمية بسبب كثافتها المرتفعة، كما تم استخراج المعادلة التفاضلية التي تعبر عن الطاقة الممتصة في الجملة وحل هذه المعادلة ثم رسم الخطوط البيانية باستخدام برنامج Mathcad ومناقشة وتحليل النتائج التي تم التوصل إليها. ودلت النتائج على تضخم الأمواج في الجملة بنتيجة الطاقة الممتصة وزيادة عدم الاستقرار فيها. We have studied in this paper, investigated the influence of an electron beam on a dense warm inhomogeneous plasma, and the instability resulting in this system, through studying of the influence of plasma density variation on the beam-plasma instability growth. Where we considered the plasma density is in the same order of Fermi gas, and we considered the model of homogeneous cold beam-inhomogeneous warm plasma system, with small phase velocity in compared with the case of existence of an external magnetic field. We derived the differential equations that describe this system in the case of collision plasma because of its high density, and we derived the differential equation that expresses the energy absorbed in the wholesale and we solved this equation then we drew the suitable graphics using Mathcad program, discussed, and analyzed the results that we reached. Results indicated an amplification of outcome waves in wholesale because of the absorbed energy and instability increasing in the system.